A study of organics and their alteration in benthic sediments of golden horn - Gonullu, MT; Bayhan, H; Avsar, Y; Arslankaya, E; Kurt, U; Tosun, I; Apaydin, O (PARLAR SCIENTIFIC PUBLICATIONS (P S P), 2003)
In 1999, an extensive sludge dredging effort to improve the on-site septic conditions and those of sea transportation via the Golden Horn has been realized. In this study the contamination levels before and after this improvement project are investigated. For this purpose, the sediment samples taken from 6 different points in the bay were analyzed for organic constituents. Meanwhile, relevant dissolved oxygen measurements from the water body (surface and just above benthic mass) at the same sampling points were made. By this way, interrelations between water body and mass of sediments are evaluated. The analytical results of sediment samples indicated that Golden Horn Bay offers convenient conditions for a productive aquatic life.
Keywords: Golden Horn; sediments; organic content; BOD; dissolved oxygen (DO); initial dissolved oxygen demand (IDOD); Environmental Sciences & Ecology